Early kingdoms Indonesian archipelago & the Malay Peninsula - Munoz, Paul Michel (Editions Didier Millet, 2016)
This book, which draws on a huge body of archaeological and documentary research, provides a much-needed overview of the history of the Malay Peninsula and insular Southeast Asia from its earliest times to the 16th century. It also provides an in-depth analysis of the international context of the political, economic and social evolution of these kingdoms, and so provides a useful background to the modern history of the region. This is an excellent book for those with a keen interest in the ancient history of the first kingdoms of the Malay Peninsula and Indonesian Archipelago.